Parametric investigation of combustion instabilities in a single-element lean direct injection combustor. (July 2019) - Gejji, Rohan M; Huang, Cheng; Fugger, Christopher; Yoon, Changjin; Anderson, William
Self-excited combustion dynamics in a liquid-fueled lean direct injection combustor at high pressure (1 MPa) are described. Studied variables include combustor and air plenum length, inlet air temperature, equivalence ratio, fuel nozzle location, and fuel composition. Measured pressure oscillations were dependent on combustor geometry and ranged from about 1% of mean chamber pressure at low equivalence ratio, up to 20% at high equivalence ratio. In the most unstable cases, strong pressure modes were measured throughout the frequency spectrum including a band around 1.2–1.5 kHz representing the 4th longitudinal mode, and another band around 7 kHz. The oscillation amplitudes have a non-monotonic dependency on air temperature, and are affected by the placement of the fuel nozzle relative to the throat of the subsonic swirling air flow. The parametric survey provides a rich dataset suitable for validating high-fidelity simulations and their subsequent use in analyzing and interpreting the complex combustion dynamics.